The negative effect of self-factors on the pre-Islamic street (Journal of the College of Basic Education, 2022)
The psyche of the pre-Islamic poet, as a realistic and sensitive poet, was affected by multiple influences.It led to the creation of an unstable, positive, defiant, strong human self, capable of confrontation at times.A negative self, incapable of confrontation at another time... However, the incapable negative self isThe subject of our study in this research, and we will address it by examining the stimulus and its specificity in poetry inIn light of the incentives produced by nature related to the factors of life. However, this privacy is not that